Role of G Protein-Coupled Receptors in Microglial Activation: Implication in Parkinson’s Disease - Gu, Chao; Chen, Yajing; Chen, Yan; Liu, Chun-Feng; Zhu, Zengyan; Wang, Mei (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is one of the prevalent neurodegenerative diseases associated with preferential loss of dopaminergic (DA) neurons in the substantia nigra compacta (SNc) and accumulation of α-synuclein in DA neurons. Even though the precise pathogenesis of PD is not clear, a large number of studies have shown that microglia-mediated neuroinflammation plays a vital role in the process of PD development. G protein-coupled receptors (GPCRs) are widely expressed in microglia and several of them act as regulators of microglial activation upon corresponding ligands stimulations. Upon α-synuclein insults, microglia would become excessively activated through some innate immune receptors. Presently, as lack of ideal drugs for treating PD, certain GPCR which is highly expressed in microglia of PD brain and mediates neuroinflammation effectively could be a prospective source for PD therapeutic intervention. Here, six kinds of GPCRs and two types of innate immune receptors were introduced, containing adenosine receptors, purinergic receptors, metabotropic glutamate receptors, adrenergic receptors, cannabinoid receptors, and melatonin receptors and their roles in neuroinflammation; we highlighted the relationship between these six GPCRs and microglial activation in PD. Based on the existing findings, we tried to expound the implication of microglial GPCRs-regulated neuroinflammation to the pathophysiology of PD and their potential to become a new expectation for clinical therapeutics.